Contribution of Fiber-Reinforced Concrete to the Sustainable Development Goals - Quesada Blasco, María Antonia; Gimeno Xipell, Victoria; Valero Ramos, Elisa (ZARCH. Journal of interdisciplinary studies in Architecture and Urbanism, 2025)
The development of fiber-reinforced concrete (FRC) structural precast elements for use in architecture is an innovative line of research that aligns with the Sustainable Development Goals (SDGs) of the 2030 Agenda. This article explores the link between their characteristics and the SDG targets related to construction. Given the importance of the production and consumption of concrete, which is universally affordable and available yet characterized by a high carbon footprint, proposals to reduce CO2 emissions in the production and use of this material could have a highly positive environmental impact. FRC can be adapted to different levels of technology, climatic conditions and budgets: this enables innovation to be transferred to countries with high social vulnerability, a key priority of the 2030 Agenda. Reducing dependence on steel in countries where it is not produced enables small manufacturers to build efficient structures using nearby resources.